Composite reduction motor housing and method of manufacturing the same

By employing a double-layer heterogeneous structure and a spiral three-dimensional cooling channel in the integrated geared motor housing, combined with a gradient transition structure for the coefficient of thermal expansion, the problems of bimetallic interface peeling and heat conduction are solved, achieving a balance between efficient heat dissipation and rigidity, and reducing the temperature of the lubricating grease and the weight of the housing.

CN122869809BActive Publication Date: 2026-11-06DONGGUAN LONGWIN PRECISION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611368918.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-11-06
Estimated Expiration
2046-09-04

AI Technical Summary

Technical Problem

Existing integrated geared motor housings present challenges in balancing rigidity and heat dissipation. In particular, the difference in thermal expansion coefficients at the bimetallic interface leads to interface peeling and difficulties in forming and cleaning fine cooling channels. At the same time, heat is difficult to effectively conduct to the reducer, affecting the working temperature of the lubricating grease and transmission accuracy.

Method used

A dual-layer heterogeneous structure is formed by adopting a low thermal conductivity iron-based inner supporting skeleton and a high thermal conductivity aluminum-based outer thermal conductive shell. A spiral three-dimensional cooling channel is set and a thermal expansion coefficient gradient transition structure is set at the interface. Convection heat transfer is enhanced through the Venturi acceleration section and the diffusion section, and a metallurgical diffusion bond is formed at the interface to relieve thermal stress.

Benefits of technology

It significantly reduces the temperature near the reducer oil chamber, improves the convective heat transfer coefficient, reduces the risk of interface peeling, and reduces the weight of the housing and the heat interception efficiency on the heat conduction path while ensuring rigidity and seismic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122869809B_ABST
    Figure CN122869809B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of motor and reducer integration structure, and discloses a composite reduction motor shell and a processing method thereof. The shell comprises an iron-based alloy inner layer bearing framework and an aluminum-based alloy outer layer heat conducting shell covering the outer layer bearing framework, three-dimensional cooling flow channels spirally extending around the stator mounting position are arranged between the two layers, the cross section of the flow channels is periodically changed along the spiral direction, and accelerating sections and diffusion sections are alternately formed; a thermal expansion coefficient gradient transition structure is arranged at the interface, and the thermal expansion coefficient gradient transition structure comprises a porous microcrystalline ceramic layer grown in situ on the surface of the inner layer bearing framework and a diffusion bonding area formed by aluminum-based alloy infiltration. The method comprises the following steps: additive manufacturing of a spiral sand core, nested positioning, laser texturing and micro-arc oxidation composite modification, vacuum low-pressure casting, sand cleaning and five-axis fine machining. The application takes into account the end stiffness and heat dissipation of the reducer, reduces the temperature of the reducer oil cavity and relieves the thermal stress of the bimetallic interface, and is suitable for integrated reduction motors of industrial robots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of integrated structure technology of motor and reducer, specifically to a composite geared motor housing and its processing method. Background Technology

[0002] As industrial robots, collaborative robots, and high-end servo equipment develop towards higher power density and higher integration, integrated geared motors that combine the servo motor and reducer in the same housing are widely used. In integrated geared motors, the motor stator generates a large amount of heat during operation, while the reducer, which is adjacent to the motor, is filled with grease. The grease is sensitive to operating temperature; excessively high temperatures can lead to a decrease in grease viscosity, oil film rupture, or even carbonization failure.

[0003] In related technologies, integrated geared motor housings are mostly made of a single material. When using iron-based alloys such as cast iron or cast steel to make the housing, the housing has high rigidity and vibration and noise reduction performance, and can withstand the alternating impact loads generated by the meshing of the gears in the reducer. However, iron-based alloys have low thermal conductivity, and the heat generated by the motor stator is difficult to dissipate outward through the housing. This causes the heat to be conducted axially along the housing towards the reducer oil cavity, and the temperature of the wall near the reducer oil cavity can easily exceed the allowable operating temperature of the lubricating grease. When using light metals such as aluminum alloys to make the housing, the housing has high thermal conductivity and light weight. However, aluminum alloys have low elastic modulus and rigidity. Under the strong radial alternating load generated by the meshing of the gears with one tooth difference in the reducer, the base of the gear ring inside the housing is prone to micro-deformation, resulting in increased gear meshing backlash and decreased transmission accuracy.

[0004] To balance rigidity and heat dissipation, some solutions attempt to form a bimetallic composite shell by covering the cast iron frame with an aluminum alloy layer. However, the significant difference in thermal expansion coefficients between cast iron and aluminum alloy leads to substantial shear stress at the bimetallic interface during repeated heating and cooling cycles, easily causing the aluminum alloy layer to peel off from the cast iron frame. Furthermore, when forming small, spirally extending cooling channels within the bimetallic shell, the core of these channels is prone to displacement or breakage during casting. The core material remaining in the channels after casting is difficult to remove, and shot blasting or acid / alkali immersion can corrode the aluminum alloy outer layer or damage the bimetallic interface. Therefore, achieving efficient heat interception along the motor's heat transfer path to the reducer while maintaining the rigidity and vibration resistance of the integrated geared motor shell, and resolving the interface peeling caused by thermal expansion mismatch at the bimetallic interface, as well as the challenges of forming and cleaning the small spiral cooling channels, are pressing technical challenges in this field. Summary of the Invention

[0005] To overcome the shortcomings and deficiencies of existing technologies, the present invention aims to provide a composite geared motor housing and its processing method. A bilayer heterogeneous structure is formed by a low thermal conductivity iron-based inner load-bearing frame and a high thermal conductivity aluminum-based outer heat-conducting shell. A spiral three-dimensional cooling channel is set at the interface of the bilayer heterogeneous structure to laterally intercept the heat conducted along the inner load-bearing frame towards the reducer. Convection heat transfer is enhanced by a Venturi acceleration section and a diffusion section formed by the periodic gradual change of the channel cross-section. Simultaneously, a gradient transition structure of thermal expansion coefficient is set between the inner load-bearing frame and the outer heat-conducting shell to alleviate thermal stress at the bimetallic interface. This integrated geared motor housing significantly reduces the operating temperature near the reducer oil cavity without sacrificing the reducer end stiffness.

[0006] This invention is achieved through the following technical solution: A composite geared motor housing includes an inner load-bearing frame and an outer heat-conducting shell covering the outer surface of the inner load-bearing frame. The inner load-bearing frame is made of an iron-based alloy, and the outer heat-conducting shell is made of an aluminum-based alloy. The thermal conductivity of the inner load-bearing frame is lower than that of the outer heat-conducting shell, forming a low thermal conductivity barrier between the motor stator mounting position and the reducer oil cavity. A three-dimensional cooling channel, spirally extending around the motor stator mounting position, is provided between the outer heat-conducting shell and the inner load-bearing frame. When the heat generated by the motor stator is conducted along the inner load-bearing frame towards the reducer oil cavity, it is laterally intercepted by the three-dimensional cooling channel at the interface between the inner load-bearing frame and the outer heat-conducting shell. The cross-section of the three-dimensional cooling channel changes periodically and gradually along the spiral extension direction, alternately forming a fluid acceleration section with a shrinking cross-sectional area and a diffusion section with a gradually expanding cross-sectional area. The fluid acceleration section constitutes a Venturi throttling structure. When the coolant flows through the fluid acceleration section, it is accelerated and washes away and thins the thermal boundary layer of the inner wall of the three-dimensional cooling channel. When it flows through the diffusion section, it decelerates and restores pressure. At the interface between the outer heat-conducting shell and the inner supporting skeleton, a transition structure is provided where the coefficient of thermal expansion gradually increases from the inner supporting skeleton to the outer heat-conducting shell. This transition structure includes a porous microcrystalline ceramic layer grown in situ on the outer surface of the inner supporting skeleton, and a diffusion bonding region formed by the aluminum-based alloy of the outer heat-conducting shell penetrating into the pores of the porous microcrystalline ceramic layer and metallurgically diffusion bonding with it. Heat intercepted by the three-dimensional cooling channels is transferred to the outer heat-conducting shell after enhanced convective heat transfer in the fluid acceleration section, where it diffuses evenly at a uniform temperature.

[0007] In the above technical solution, the inner load-bearing frame is made of iron-based alloy. Iron-based alloy has high stiffness, yield strength, and vibration and noise reduction performance, and can withstand the radial alternating load generated by the gear meshing of the reducer. At the same time, the relatively low thermal conductivity of iron-based alloy forms a low thermal conduction barrier between the motor stator mounting position and the reducer oil cavity, slowing down the speed at which the motor heat is conducted axially from the housing towards the reducer. The outer heat-conducting shell is made of aluminum-based alloy. Aluminum-based alloy has high thermal conductivity and low density. It covers the outside of the inner load-bearing frame, which not only reduces the overall weight of the shell, but also rapidly and evenly diffuses the heat transferred to the outer layer after heat exchange through the three-dimensional cooling channels. The three-dimensional cooling channels are arranged at the interface between the inner load-bearing frame and the outer heat-conducting shell, spirally extending around the motor stator mounting position. This allows the heat conducted along the inner load-bearing frame towards the reducer to be intercepted laterally by the cooling medium on the conduction path, rather than continuing to be conducted axially to the reducer oil cavity.

[0008] The cross-section of the three-dimensional cooling channel changes periodically and gradually along the spiral direction, with adjacent contraction and expansion sections forming a Venturi throttling structure. In the fluid acceleration section where the cross-sectional area contracts, the coolant velocity increases, and the high-speed fluid scours the inner wall of the three-dimensional cooling channel, thinning the thermal boundary layer and reducing the convective heat transfer resistance between the inner wall and the coolant. Upon entering the diffusion section where the cross-sectional area expands, the coolant velocity decreases and the pressure rises, while local vortices form within the diffusion section, disturbing the thermal boundary layer at the inlet of the adjacent acceleration section. This periodic repetition results in a significantly higher overall convective heat transfer coefficient along the spiral direction for the three-dimensional cooling channel compared to a straight pipe channel with a uniform cross-section.

[0009] At the interface between the outer heat-conducting shell and the inner load-bearing frame, a transition structure is provided with an increasing coefficient of thermal expansion along the direction from the inner load-bearing frame to the outer heat-conducting shell. The porous microcrystalline ceramic layer in the transition structure grows in situ on the outer surface of the inner load-bearing frame, with a coefficient of thermal expansion between that of iron-based alloys and aluminum-based alloys. This creates a gradient of thermal expansion coefficients at the bimetallic interface, allowing the thermal stress generated during the motor's heating and cooling cycles to be released gradually along the interface thickness direction, rather than concentrating at the direct interface between the iron-based and aluminum-based alloys. Under casting pressure, the aluminum-based alloy penetrates into the pores of the porous microcrystalline ceramic layer and undergoes elemental interdiffusion with the ceramic phase on the inner wall of the pores, forming a metallurgical diffusion bonding zone. This results in not only geometric nesting between the porous microcrystalline ceramic layer and the outer heat-conducting shell but also metallurgical bonding, thus enhancing the interfacial bonding strength.

[0010] The heat captured by the three-dimensional cooling channels is transferred to the outer heat-conducting shell after enhanced convective heat transfer in the fluid acceleration section. Then, the heat is diffused evenly along the circumference and axial direction of the aluminum-based outer heat-conducting shell by the high thermal conductivity shell to the outer surface for dissipation into the environment. As a result, the heat generated by the motor stator is carried away by the cooling medium at the interface before it is conducted to the reducer oil chamber, and the temperature of the wall near the reducer oil chamber is significantly reduced.

[0011] Preferably, the cross-section of the three-dimensional cooling channel is elliptical, and the ratio of the maximum cross-sectional area of ​​the three-dimensional cooling channel to the minimum cross-sectional area of ​​the fluid acceleration section is 1.35 to 2.15. In the above technical solution, the elliptical cross-section transitions smoothly when gradually changing along the spiral direction, making it less likely to generate local dead water zones; the ratio of the maximum cross-sectional area to the minimum cross-sectional area, i.e., the cross-sectional contraction ratio, is controlled within the range of 1.35 to 2.15, which ensures that the fluid acceleration section has sufficient Venturi acceleration effect, while avoiding an excessively large contraction ratio that would cause the flow resistance pressure drop to exceed the head of the coolant supply device.

[0012] Preferably, the ratio of the maximum cross-sectional area to the minimum cross-sectional area is between 1.50 and 1.80. Within this ratio range, the Venturi effect in the fluid acceleration section increases the convective heat transfer coefficient by more than double compared to a straight pipe with a constant cross-section, while the flow resistance pressure drop remains within the head range of the coolant supply device. In the above technical solution, when the cross-sectional area reduction ratio is in the range of 1.50 to 1.80, the benefit of a significant increase in the convective heat transfer coefficient with increasing reduction ratio still outweighs the cost of increased flow resistance pressure drop, and the overall energy efficiency ratio is in the peak range.

[0013] Preferably, the fluid acceleration section and diffusion section are alternately distributed along the spiral direction with a period of one pitch, so that the coolant undergoes one acceleration-diffusivity cycle in each pitch cycle and periodically disturbs the thermal boundary layer. The pitch of the three-dimensional cooling channel is 18 mm to 36 mm, and the equivalent diameter is 3.5 mm to 6.5 mm. In the above technical solution, the values ​​of pitch and equivalent diameter are adapted to the axial length of the stator of the integrated servo motor, which is 50 mm to 120 mm, so that the cooling medium forms 2 to 5 complete heat exchange cycles in the core heat-generating area of ​​the stator; the equivalent diameter is in the millichannel range, and the three-dimensional cooling channel has a large specific surface area.

[0014] Preferably, the outer surface of the inner supporting skeleton is formed with an array of laser-textured micropits recessed into the inner supporting skeleton matrix. A porous microcrystalline ceramic layer covers the outer surface of the inner supporting skeleton and the inner walls of the laser-textured micropits. The aluminum-based alloy of the outer heat-conducting shell fills the laser-textured micropits and is continuously integrated with the aluminum-based alloy that penetrates into the pores of the porous microcrystalline ceramic layer, forming a mechanically interlocked network spanning micrometer to hundred-micrometer scales. The aperture of the laser-textured micropits is 60 micrometers to 120 micrometers, the center-to-center distance between adjacent laser-textured micropits is 250 micrometers to 400 micrometers, and the depth of the laser-textured micropits is 150 micrometers to 250 micrometers. The thickness of the porous microcrystalline ceramic layer is 15 micrometers to 35 micrometers, the porosity is 18% to 28%, and the average pore size is 2 micrometers to 8 micrometers.

[0015] In the above technical solution, laser-textured micropits are recessed into the inner load-bearing skeleton matrix, with a scale of hundreds of micrometers. After the aluminum-based alloy fills the micropits, it forms a rivet structure with anchoring effect along both the interface normal and tangential directions, bearing the large-scale shear load at the interface. A porous microcrystalline ceramic layer covers the outer surface of the inner load-bearing skeleton and the inner wall of the micropits, with a scale of micrometers. The aluminum-based alloy penetrates into the ceramic pores and forms a metallurgical diffusion bond, bearing the small-scale shear and thermal stress at the interface. The aluminum-based alloy filling the laser-textured micropits and the aluminum-based alloy penetrating into the pores of the porous microcrystalline ceramic layer are filled and solidified simultaneously during casting, becoming a continuous whole. This makes the hundreds-micrometer-scale rivet structure and the micrometer-scale ceramic pore interlocking structure spatially connected and inseparable, forming a mechanical interlocking network spanning the micrometer to hundreds-micrometer scale, with an interface shear strength of over 45 MPa.

[0016] Preferably, the inner load-bearing frame is made of QT500-7 ductile iron or 42CrMo alloy steel, and the outer heat-conducting shell is made of ZL101A cast aluminum alloy. In the above technical solution, QT500-7 ductile iron combines high rigidity, good vibration and noise reduction performance, and casting and machining performance, making it suitable for standard load conditions; 42CrMo alloy steel has higher yield strength, making it suitable for heavy-duty industrial robot conditions; and ZL101A cast aluminum alloy has good fluidity, and after T6 heat treatment, its mechanical strength and thermal conductivity are balanced.

[0017] The present invention also provides a method for processing the above-mentioned composite geared motor housing, comprising the following steps.

[0018] S1. Based on the preset three-dimensional cooling channel shape, a spiral sand core is integrally formed using additive manufacturing technology. The sand core has the tensile strength required to support the spiral cantilever structure at room temperature, and after solidification upon contact with molten aluminum alloy, the sand core self-collapses to a residual strength that can be removed by the fluid.

[0019] S2. Position the sand core nested on the outer surface of the iron-based alloy inner layer load-bearing skeleton, and place the nested inner layer load-bearing skeleton inside the casting cavity.

[0020] S3. Perform interface composite modification treatment on the outer surface of the inner layer support skeleton: First, use laser to process a micro-pit array on the outer surface of the inner layer support skeleton, and then perform micro-arc oxidation treatment on the surface of the inner layer support skeleton with the micro-pit array to grow a porous microcrystalline ceramic layer in situ on the outer surface of the inner layer support skeleton and the inner wall of the micro-pits.

[0021] S4. After evacuating the casting cavity, inject molten aluminum-based alloy liquid into the casting cavity under low pressure. Under low pressure, the aluminum-based alloy liquid simultaneously penetrates into the micropores and micro-pits of the porous microcrystalline ceramic layer. After pressure holding and solidification, it forms an outer heat-conducting shell that is metallurgically and mechanically combined with the inner load-bearing skeleton.

[0022] S5. After demolding, remove the collapsed sand core to obtain a composite shell blank with three-dimensional cooling channels inside.

[0023] S6. Using the axis of the motor stator mounting hole as a reference, perform five-axis linkage adaptive precision machining on the composite housing blank.

[0024] In the above processing method, step S1 uses additive manufacturing to integrally form a sand core with a spiral cantilever structure, avoiding flash and misalignment at the parting surface caused by splicing separate sand cores. The sand core has the tensile strength required to support the spiral cantilever structure at room temperature, and does not break or shift during handling, preheating, and the initial stage of casting. Upon contact with the molten aluminum alloy and after the binder pyrolyzes and carbonizes following the solidification of the casting, it self-collapses, and its residual strength decreases to a level that can be removed by the fluid, creating conditions for subsequent removal of the core from the spiral flow channel with an equivalent diameter of only a few millimeters. Step S3 first performs laser texturing and then micro-arc oxidation, so that the porous microcrystalline ceramic layer not only covers the planar area of ​​the inner supporting skeleton, but also covers the inner wall of the laser texturing micro-pits; if the process sequence is reversed, subsequent laser processing will destroy the already formed ceramic layer. In step S4, the molten aluminum alloy simultaneously penetrates the micron-sized pores and hundred-micron-sized laser-textured micropits of the porous microcrystalline ceramic layer under low pressure, making the aluminum alloy in both locations a continuous melt during the filling stage. After solidification, this forms a continuous, cross-scale mechanical interlocking network. Step S6 uses the axis of the motor stator mounting hole as a unified finishing datum to eliminate positional deviations caused by the different shrinkage rates of the two materials during bimetallic casting.

[0025] Preferably, in step S1, the molding raw materials for the sand core include 100-200 mesh abrasive sand, 1.2-1.8% modified furan resin binder by mass of the abrasive sand, and 15-25% sulfonic acid microcapsule curing agent by mass of the modified furan resin binder. The molded sand core has a room temperature tensile strength of 2.8 MPa to 4.2 MPa. After solidification by casting with aluminum-based alloy liquid, the residual strength of the sand core drops to below 0.5 MPa.

[0026] Preferably, in step S3, a silicate-aluminate composite electrolyte is used for micro-arc oxidation treatment, with a pulse voltage of 450 volts to 600 volts, a current density of 5 amperes per square decimeter to 15 amperes per square decimeter, and a treatment time of 10 to 20 minutes. The diameter of the laser-processed micro-pits is 60 micrometers to 120 micrometers, the center-to-center distance of the laser-processed micro-pits is 250 micrometers to 400 micrometers, and the depth of the laser-processed micro-pits is 150 micrometers to 250 micrometers. Micro-arc oxidation on an iron-based alloy substrate using a silicate-aluminate composite electrolyte generates a porous microcrystalline ceramic layer rich in silicon and aluminum elements, exhibiting good metallurgical affinity with the aluminum-based alloy melt.

[0027] Preferably, in step S4, the inner supporting skeleton is preheated to 380°C to 450°C before being placed in the casting cavity; the pouring temperature of the aluminum-based alloy liquid is 710°C to 740°C; the vacuum degree of the casting cavity is -0.08 MPa to -0.095 MPa; the low-pressure injection pressure is 0.06 MPa to 0.12 MPa with a pressure increase rate of 0.015 MPa per second; the holding time is 120 seconds to 180 seconds; and the solidification temperature gradient is 15°C to 25°C per centimeter. In step S5, the sand core is removed using an N-methylpyrrolidone-based organic solvent supplemented with ultrasonic vibration at 28 kHz to 40 kHz; the organic solvent temperature is 60°C to 75°C; and the removal time is 15 minutes to 25 minutes. In the above technical solution, preheating the inner supporting skeleton can reduce the instantaneous temperature difference when the aluminum-based alloy liquid comes into contact with the inner supporting skeleton, avoiding cold shuts and excessively thick brittle intermetallic compounds; evacuating the casting cavity can remove trace amounts of gas generated by the heated sand core, reducing porosity and pinhole defects; the directional sequential solidification temperature gradient ensures that the casting solidifies sequentially from the end away from the gate to the gate end, avoiding shrinkage cavities and porosity. N-methylpyrrolidone-based organic solvent has a swelling and peeling effect on the residual carbon from the pyrolysis of the sand core binder, and is chemically inert to both iron-based and aluminum-based alloys. Combined with the ultrasonic cavitation effect, the disintegrated sand core can be removed from the fine spiral flow channel without corroding the outer aluminum-based alloy or damaging the bimetallic composite interface.

[0028] Compared with related technologies, the present invention has the following beneficial effects.

[0029] First, this invention forms a low thermal conductivity barrier between the motor stator mounting location and the reducer oil cavity by using a low thermal conductivity iron-based alloy inner layer support skeleton. Furthermore, a three-dimensional cooling channel extending spirally around the motor stator mounting location is set at the double-layer heterogeneous interface. This intercepts the heat conducted along the inner layer support skeleton towards the reducer laterally along the conduction path, significantly reducing the wall temperature near the reducer oil cavity. Under operating conditions of 800 watts of motor stator heating power and a cooling medium flow rate of 1.5 liters per minute, compared to an all-cast iron casing, the highest wall temperature near the reducer oil cavity is reduced from 85.4 degrees Celsius to 69.8 degrees Celsius.

[0030] Secondly, this invention utilizes a periodically varying cross-section of the flow channel to create a Venturi structure alternating between acceleration and diffusion sections. This allows the cooling medium to thin the thermal boundary layer by scouring the flow path in the acceleration section and to generate vortex disturbances in the diffusion section, resulting in a significant improvement in the overall convective heat transfer coefficient compared to a straight pipe with a uniform cross-section. When the cross-sectional area reduction ratio is 1.65, the convective heat transfer coefficient increases from approximately 3150 W / m² Kelvin for a straight pipe with a uniform cross-section to approximately 6950 W / m² Kelvin, more than doubling.

[0031] Third, this invention alleviates the interfacial shear stress caused by the difference in thermal expansion coefficients between iron-based alloys and aluminum-based alloys by setting a transition structure at the bimetallic interface with a gradient increase in the coefficient of thermal expansion from the inner load-bearing skeleton to the outer heat-conducting shell, and forming a gradient transition with a porous microcrystalline ceramic layer and a metallurgical diffusion bonding region; at the same time, the laser-textured micro-pits and the aluminum-based alloy continuously integrated in the ceramic pores form a mechanical interlocking network spanning the micrometer to hundred-micrometer scale, and the interfacial shear strength can reach more than 45 MPa, reducing the risk of interfacial delamination during temperature cycling.

[0032] Fourth, the inner layer of the composite geared motor housing of the present invention uses an iron-based alloy to ensure the rigidity and shock resistance of the reducer end, while the outer layer uses an aluminum-based alloy to reduce weight and dissipate heat evenly. Under the premise of consistent housing shape and volume, the weight is reduced from 8.65 kg to 5.62 kg compared with the all-cast iron housing, a weight reduction of about 35%. Under the simulation condition of extreme impact load with a radial concentrated force of 15000 N, the maximum radial deformation at the root circle of the inner layer bearing skeleton is about 0.0076 mm, which still meets the backlash requirement of cycloidal pinwheel meshing.

[0033] Fifth, the processing method of this invention uses additive manufacturing of spiral sand cores that have strength at room temperature and self-collapse at high temperature, and uses N-methylpyrrolidone-based organic solvents that are chemically inert to both iron-based and aluminum-based alloys in conjunction with ultrasonic sand removal, which solves the problem of forming and removing small spiral flow channel cores with an equivalent diameter of only 3.5 mm to 6.5 mm; five-axis linkage adaptive precision machining is performed with the axis of the motor stator mounting hole as the reference, and the coaxiality of the bearing seat hole at the front end of the finished product relative to the stator mounting hole can be controlled within 0.003 mm to 0.005 mm. Attached Figure Description

[0034] The present invention will be further described with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the present invention. For those skilled in the art, other drawings can be obtained based on the following drawings without creative effort.

[0035] Figure 1 This is an axial cross-sectional view of the composite geared motor housing provided in an embodiment of the present invention.

[0036] Figure 2 for Figure 1 A schematic diagram of the radial cross-section of section A-A.

[0037] Figure 3 This is a schematic diagram of the gradual change of the cross-section of the three-dimensional cooling channel after it is unfolded along the spiral direction, as provided in an embodiment of the present invention.

[0038] Figure 4 This is a schematic diagram of the performance curves relating the cross-sectional shrinkage ratio, convective heat transfer coefficient, and flow channel pressure drop, provided for embodiments of the present invention.

[0039] Figure 5 This is an enlarged schematic diagram of the microstructure at the interface between the inner load-bearing skeleton and the outer heat-conducting shell, as provided in an embodiment of the present invention.

[0040] Figure 6 This is a flowchart illustrating the composite geared motor housing processing method provided in an embodiment of the present invention.

[0041] Figure 7 The diagram shows the temperature changes over time at the inner layer load-bearing skeleton temperature measurement point and the aluminum-based alloy temperature measurement point during the composite casting process provided in this embodiment of the invention. Detailed Implementation

[0042] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0043] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0044] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0045] Example 1 This embodiment provides a composite geared motor housing, suitable for integrated servo geared motors of standard load industrial robots or collaborative robots.

[0046] Reference Figure 1 and Figure 2As shown, the composite geared motor housing has an overall cylindrical structure extending along the X-axis, including an inner load-bearing frame 1 and an outer heat-conducting shell 2 covering the outer surface of the inner load-bearing frame 1. The inner load-bearing frame 1 is made of QT500-7 ductile iron, and the outer heat-conducting shell 2 is made of ZL101A cast aluminum alloy and has undergone T6 heat treatment. QT500-7 ductile iron has a thermal conductivity of approximately 32 W / m Kelvin, a coefficient of thermal expansion of approximately 12.5 × 10⁻⁶ Kelvin, and a density of approximately 7.10 g / cm³ within a temperature range of 20°C to 200°C. ZL101A cast aluminum alloy has a thermal conductivity of approximately 155 W / m Kelvin, a coefficient of thermal expansion of approximately 21.5 × 10⁻⁶ Kelvin, and a density of approximately 2.68 g / cm³ within the same temperature range. The thermal conductivity of the inner load-bearing frame 1 is significantly lower than that of the outer heat-conducting shell 2, resulting in a large axial thermal resistance between the middle section of the shell where the motor stator mounting position is located and the front end of the shell where the reducer oil cavity is located, thus forming a low thermal conduction barrier between the motor stator mounting position and the reducer oil cavity.

[0047] The inner surface of the inner load-bearing frame 1 is sequentially provided with a motor stator mounting position and a reducer internal gear ring base along the axial direction. The motor stator is press-fitted into the motor stator mounting position, and the reducer cycloidal pinwheel or planetary gear mechanism is installed in the internal gear ring base and the front bearing seat hole. The outer heat-conducting shell 2 is coated on the outer surface of the inner load-bearing frame 1 by low-pressure composite casting, forming a metallurgical-mechanical composite bond with the inner load-bearing frame 1 during the casting process. The outer surface of the outer heat-conducting shell 2 can be provided with heat dissipation fins or a flat mounting surface as needed; this embodiment does not limit the specific shape of the outer surface.

[0048] Reference Figure 1 , Figure 2 and Figure 3 As shown, a three-dimensional cooling channel 3, spirally extending around the motor stator mounting position, is provided between the outer heat-conducting shell 2 and the inner supporting frame 1. The three-dimensional cooling channel 3 extends along the outer cylindrical surface of the inner supporting frame 1 in a single-line spiral manner, with the spiral axis coinciding with the motor axis X. The cross-section of the three-dimensional cooling channel 3 is elliptical, with the major axis of the elliptical cross-section extending approximately circumferentially along the inner supporting frame 1. The equivalent diameter of the three-dimensional cooling channel 3 is 5.0 mm, and the pitch is 24 mm. In an integrated servo geared motor with a stator axial length of approximately 80 mm to 100 mm, the above pitch allows the cooling medium to form approximately three complete spiral cycles in the stator heat-generating core area.

[0049] The cross-section of the three-dimensional cooling channel 3 changes periodically and gradually along the spiral extension direction. Along the spiral direction, two adjacent cross-sections are respectively the outlet cross-section of the diffuser section with the largest cross-sectional area and the throat cross-section of the fluid acceleration section with the smallest cross-sectional area, forming a fluid acceleration section 31 with a shrinking cross-sectional area and a diffuser section 32 with a gradually expanding cross-sectional area between them. The fluid acceleration section 31 and the diffuser section 32 are alternately distributed with a period of one pitch. In this embodiment, the ratio of the maximum cross-sectional area of ​​the three-dimensional cooling channel 3 to the minimum cross-sectional area of ​​the fluid acceleration section 31, i.e., the cross-sectional shrinkage ratio, is taken as 1.65. When the cross-sectional shrinkage ratio is 1.65, the major axis of the ellipse at the diffuser section outlet is approximately √1.65 times the major axis of the throat ellipse, and the minor axis is scaled proportionally. The cooling medium is a 50% (v / v) ethylene glycol aqueous solution, with a coolant inlet temperature of 25 degrees Celsius and an inlet flow rate of 1.5 liters per minute.

[0050] Reference Figure 5 As shown, a transition structure 4 is provided at the interface between the outer heat-conducting shell 2 and the inner supporting skeleton 1. The transition structure 4 comprises three layers along the direction from the inner supporting skeleton 1 to the outer heat-conducting shell 2: the first layer is an array of laser-textured micropits 11 recessed into the substrate of the inner supporting skeleton 1; the second layer is a porous microcrystalline ceramic layer 41 grown in situ on the outer surface of the inner supporting skeleton 1 and the inner wall of the laser-textured micropits 11; the third layer is a diffusion bonding region 42 formed by the aluminum-based alloy of the outer heat-conducting shell 2 penetrating into the pores of the porous microcrystalline ceramic layer 41 and metallurgically diffusion bonding with the porous microcrystalline ceramic layer 41. In this embodiment, the porous microcrystalline ceramic layer 41 is generated by a micro-arc oxidation process, with a film thickness of 25 micrometers, a porosity of approximately 23%, and an average pore diameter of approximately 5 micrometers. The diameter of the laser-textured micropits 11 is approximately 90 micrometers, the center-to-center distance between adjacent micropits is approximately 320 micrometers, and the depth is approximately 200 micrometers. Under casting pressure, aluminum-based alloy fills the laser-textured micro-pits 11 and simultaneously penetrates the pores of the porous microcrystalline ceramic layer 41. After solidification, the aluminum-based alloy columns filling the laser-textured micro-pits 11 are continuous with the aluminum-based alloys penetrating the pores of the porous microcrystalline ceramic layer 41, forming a mechanical interlocking network spanning the micrometer to hundred-micrometer scale.

[0051] The working principle of this embodiment is as follows. When the integrated geared motor is running, part of the heat generated by the motor stator is transferred to the inner bearing frame 1 through the mating surface between the stator and the inner bearing frame 1. Since the inner bearing frame 1 is made of QT500-7 ductile iron with a low thermal conductivity, the speed at which the heat transferred to the inner bearing frame 1 is conducted along the housing axis X towards the reducer oil cavity is suppressed by the low thermal conductivity barrier. The three-dimensional cooling channel 3 is arranged at the interface between the inner bearing frame 1 and the outer heat-conducting housing 2 and surrounds the motor stator mounting position, so that the heat conducted axially along the inner bearing frame 1 is laterally intercepted by the cooling medium flowing in the three-dimensional cooling channel 3 before reaching the reducer oil cavity.

[0052] The cooling medium flows spirally within the three-dimensional cooling channel 3, passing through a fluid acceleration section 31 with a shrinking cross-sectional area and a diffusion section 32 with a gradually expanding cross-sectional area in each pitch cycle. In the acceleration section 31, the cooling medium velocity increases as the cross-sectional area decreases, and the high-speed fluid creates a normal scouring effect on the inner wall of the three-dimensional cooling channel 3, thinning the thermal boundary layer and increasing the convective heat transfer coefficient from the inner wall to the cooling medium. In the diffusion section 32, the cooling medium velocity decreases, the static pressure increases, and small-scale vortices form near the wall due to the gradually expanding cross-sectional area. These vortices draw the low-temperature fluid from the center of the channel to the near-wall region, disturbing the thermal boundary layer at the inlet of the next acceleration section. This periodic repetition results in a significantly higher overall convective heat transfer coefficient along the entire spiral length of the three-dimensional cooling channel 3 compared to a straight pipe channel with a uniform cross-section. According to simulation results based on computational fluid dynamics, under the boundary conditions of equivalent diameter of 5.0 mm, pitch of 24 mm, and inlet flow rate of 1.5 L / min, the convective heat transfer coefficient is approximately 6950 W / m² Kelvin when the cross-sectional area shrinkage ratio is 1.65, while the convective heat transfer coefficient of a straight pipe with uniform cross-section is approximately 3150 W / m² Kelvin, an increase of about 1.2 times.

[0053] The heat trapped by the cooling medium is transferred to the cooling medium through the inner wall of the three-dimensional cooling channel 3, and the cooling medium carries the heat out of the shell along the spiral channel. At the same time, some heat is transferred to the outer heat-conducting shell 2 through the interface transition structure 4. Since the thermal conductivity of ZL101A cast aluminum alloy is about 4.8 times that of QT500-7 ductile iron, the heat transferred to the outer heat-conducting shell 2 diffuses rapidly and uniformly along the circumference and axial direction of the outer heat-conducting shell 2, and dissipates to the surrounding environment through the outer surface of the outer heat-conducting shell 2. As a result, the heat generated by the motor stator is diverted and carried away by the cooling medium and the outer heat-conducting shell 2 before it is conducted to the reducer oil cavity, and the wall temperature near the reducer oil cavity is significantly reduced.

[0054] During the temperature cycle of repeated motor starts, full-load operation, and shutdown cooling, the temperatures of the inner load-bearing frame 1 and the outer heat-conducting shell 2 change with the motor's operating conditions. Because the thermal expansion coefficients of QT500-7 ductile iron and ZL101A cast aluminum alloy differ significantly, direct bonding of the two metals would generate substantial shear stress at the bonding surface during temperature changes. In this embodiment, the porous microcrystalline ceramic layer 41 is located between the iron-based alloy and the aluminum-based alloy. The equivalent thermal expansion coefficient of the porous microcrystalline ceramic layer 41 is between that of QT500-7 ductile iron and ZL101A cast aluminum alloy, and the porous structure itself possesses a certain deformation coordination capability, allowing the interfacial thermal stress to be released gradually along the thickness direction of the ceramic layer. The aluminum-based alloy, penetrating the pores of the porous microcrystalline ceramic layer 41, undergoes interdiffusion of elements such as silicon and aluminum with the ceramic phase, forming a diffusion bonding region 42 that connects the iron-based alloy, ceramic layer, and aluminum-based alloy into a continuous whole. The aluminum-based alloy pillars filling the laser-textured micropits 11 bear the interfacial shear load at the hundred-micrometer scale, while the aluminum-based alloy penetrating the ceramic pores bears the interfacial shear and thermal stress at the micrometer scale. The aluminum-based alloy phases at both scales are continuous, jointly forming a cross-scale mechanical interlocking network. Testing shows that the interfacial shear strength of the composite shell in this embodiment can reach over 45 MPa.

[0055] By adopting the above technical solution, the composite geared motor housing of this embodiment significantly reduces the working temperature near the oil chamber of the geared motor while ensuring the rigidity and shock resistance of the geared motor end, and the bimetallic interface is not easy to peel off under temperature cycling.

[0056] Example 2 This embodiment provides a composite geared motor housing, which differs from Embodiment 1 in that the inner load-bearing frame 1 is made of 42CrMo alloy steel, and is suitable for heavy-duty industrial robots with a load of more than 200 kg.

[0057] The thermal conductivity of 42CrMo alloy steel is approximately 42.5 W / m Kelvin in the temperature range of 20°C to 200°C, its coefficient of thermal expansion is approximately 12.2 × 10⁻⁶ Kelvin, and its density is approximately 7.85 g / cm³. Compared with QT500-7 ductile iron, 42CrMo alloy steel has a higher yield strength, allowing for further thinning of the wall thickness of the internal gear ring base, which is beneficial for reducing the weight and rotational inertia of the end effector of heavy-duty industrial robots. The thermal conductivity of 42CrMo alloy steel is still significantly lower than that of ZL101A cast aluminum alloy (155 W / m Kelvin), while its coefficient of thermal expansion is similar to that of QT500-7. Therefore, the low thermal conductivity barrier, gradient transition structure of thermal expansion coefficient, and cross-scale mechanical interlocking network described in Example 1 are also valid in this example.

[0058] In this embodiment, the pitch of the three-dimensional cooling channel 3 is 18 mm to accommodate the large stator heating power and long stator axial length of the heavy-duty motor; the cross-sectional shrinkage ratio is 1.50. Simulation calculations show that, under conditions of higher stator heating power, the convective heat transfer coefficient of this embodiment can still be increased by more than two times compared to a straight pipe with a uniform cross-section, while the flow resistance pressure drop remains within the head range of the matched micro-pump.

[0059] By employing the above technical solution, this embodiment can still control the wall temperature near the reducer oil chamber within the allowable operating temperature range of the lubricating grease under heavy-load conditions, while simultaneously meeting the stiffness requirements of heavy-load gear meshing. The remaining structure and working principle of this embodiment are the same as those of Embodiment 1, and will not be repeated here.

[0060] Example 3 This embodiment provides a processing method for the composite geared motor housing as described in Embodiment 1, referring to... Figure 6 As shown, it includes steps S1 to S6.

[0061] Step S1: Molding the Spiral Sand Core. Based on the pre-designed three-dimensional cooling channel shape, a spiral sand core is integrally molded using 3D printing additive manufacturing technology. The raw material for the sand core is 100-200 mesh high-roundness granular sand as the aggregate, with 1.5% (by weight of the granular sand) of low-gas-emission modified furan resin added as a binder, and 20% (by weight of the modified furan resin) of sulfonic acid composite microcapsule curing agent added. The core is formed after sand mixing, 3D printing powder spreading, and spray curing. Granular sand has a low coefficient of thermal expansion, high refractoriness, and good sphericity, which helps ensure a smooth inner wall of the spiral channel with an equivalent diameter of several millimeters, reducing flow resistance. The high-temperature gas evolution of the modified furan resin is no more than 12 ml / g, which reduces porosity defects during casting.

[0062] The formed sand core has a tensile strength of approximately 3.5 MPa at room temperature, which is sufficient to support the cantilevered spiral mesh sand core under its own weight and minor impacts during handling, mold closing, and preheating. After the sand core is in contact with molten aluminum-based alloy at approximately 725 degrees Celsius and solidifies with the casting, the modified furan resin binder undergoes pyrolysis and carbonization, reducing the residual strength of the sand core to below 0.5 MPa. This causes the sand core to be in a collapsible state after cooling, allowing it to be flushed out by fluid through the three-dimensional cooling channels.

[0063] Step S2, Nesting and Positioning. The formed and inspected spiral sand core is nested and positioned within the pre-set sand core positioning groove on the outer surface of the iron-based alloy inner supporting skeleton 1. Both ends of the sand core extend beyond the two end faces of the inner supporting skeleton 1, forming sand core support heads. The inner supporting skeleton 1 with the nested sand core is placed in the preheated metal casting cavity, the mold is closed, and it is locked.

[0064] Step S3: Interface composite modification treatment. Before placing the inner layer support skeleton 1 into the casting cavity, the outer surface of the inner layer support skeleton 1 is first subjected to interface composite modification treatment.

[0065] The first step is laser texturing. An industrial-grade nanosecond fiber laser with a power of approximately 400 watts and a scanning speed of approximately 1800 mm / s is used to fabricate an array of micropits on the outer surface of the inner supporting skeleton 1. The laser-textured micropits 11 have an aperture of approximately 90 micrometers, a center-to-center distance of approximately 320 micrometers between adjacent micropits, and a depth of approximately 200 micrometers. The morphology of the laser-textured micropits 11 is approximately inverted conical, with rough pit walls.

[0066] The second step is micro-arc oxidation. The laser-textured inner support skeleton 1 is placed in a silicate-aluminate composite electrolyte and treated for about 15 minutes with a pulse voltage of about 520 volts and a current density of about 10 amperes per square decimeter. This results in the in-situ growth of a porous microcrystalline ceramic layer 41 rich in silicon and aluminum on the iron-containing substrate surface. The porous microcrystalline ceramic layer 41 has a thickness of about 25 micrometers, a porosity of about 23%, and an average pore size of about 5 micrometers. Since micro-arc oxidation is performed after laser texturing, the porous microcrystalline ceramic layer 41 not only covers the planar area of ​​the inner support skeleton 1 but also the inner wall of the laser-textured micro-pits 11.

[0067] Step S4: Low-pressure composite casting. The inner supporting skeleton 1, which has undergone interface composite modification treatment and is preheated to 420 degrees Celsius, is placed in the casting cavity. After mold closing, the casting cavity is evacuated to a vacuum degree of approximately -0.09 MPa to remove the gas adsorbed in the cavity and on the surface of the sand core. Then, dry compressed air is introduced into the casting cavity at a pressurization rate of 0.015 MPa per second. ZL101A aluminum-based alloy liquid at a temperature of 725 degrees Celsius is injected into the cavity at a low pressure of approximately 0.09 MPa. Under pressure, the aluminum-based alloy liquid simultaneously penetrates the micron-sized pores of the porous microcrystalline ceramic layer 41 and the hundred-micron-sized laser-textured micro-pits 11. After filling, the pressure is held for approximately 150 seconds to allow the aluminum-based alloy liquid to continuously receive liquid feeding during solidification and shrinkage. The casting cavity adopts a directional sequential solidification design, with the solidification temperature gradient controlled at approximately 20 degrees Celsius per centimeter, allowing the casting to solidify sequentially from the end furthest from the gate to the gate end, resulting in a dense aluminum-based alloy microstructure around the spiral three-dimensional cooling channel.

[0068] Reference Figure 7As shown, at the instant of pouring, the temperature of the inner skeleton measuring point is 420 degrees Celsius, and the temperature of the aluminum-based alloy liquid measuring point is 725 degrees Celsius. About 15 seconds after pouring, due to the rapid heat release of the aluminum-based alloy liquid to the inner supporting skeleton 1, the temperature of the inner skeleton measuring point rises to an instantaneous peak of about 510 degrees Celsius, and the temperature of the aluminum-based alloy measuring point drops to about 680 degrees Celsius. During this stage, the aluminum-based alloy liquid penetrates into the pores of the porous microcrystalline ceramic layer 41 and the laser-textured micro-pits 11 under pressure. About 60 seconds after pouring, the temperature of the inner skeleton measuring point is about 480 degrees Celsius, and the temperature of the aluminum-based alloy measuring point is about 590 degrees Celsius, which is in the low-pressure holding and feeding stage. About 150 seconds after pouring, the temperature of the aluminum-based alloy measuring point drops to about 460 degrees Celsius, exceeding the eutectic solidification point of the aluminum-based alloy, and the holding pressure ends. About 300 seconds after pouring, the casting temperature drops to below about 200 degrees Celsius, which meets the conditions for demolding.

[0069] Step S5: Non-destructive sand removal. After the casting cools and is demolded, the entire composite shell is immersed in an N-methylpyrrolidone-based composite organic solvent bath at approximately 70 degrees Celsius, and ultrasonic vibration at a frequency of approximately 35 kHz is applied for about 20 minutes. The N-methylpyrrolidone-based organic solvent has a strong swelling and peeling effect on the modified furan resin pyrolysis residue in the sand core, while being chemically inert to both QT500-7 ductile iron and ZL101A cast aluminum alloy. The ultrasonic cavitation effect generates micro-jets and shock waves in the three-dimensional cooling channel, peeling the dispersed abrasive sand particles from the inner wall of the channel and discharging them from both ends of the channel with the solvent flow. After treatment, the sand core removal rate in the three-dimensional cooling channel can reach over 99.9%, and the outer aluminum-based alloy and interface transition structure 4 are not corroded or damaged.

[0070] Step S6: Five-axis adaptive finishing. Using the central axis of the motor stator mounting hole as reference A, the sand-cleaned composite housing blank is clamped in a five-axis machining center. An online probe measures the actual position of each key surface of the blank. The tool path is automatically compensated based on the actual deformation caused by the difference in shrinkage rates between the two materials after bimetallic casting. The front bearing seat hole, internal gear ring base, and mounting flange of the reducer are then finished. The finished products are inspected using a Hexagon coordinate measuring machine. Ten finished products are randomly sampled, and the coaxiality error of the high-precision bearing seat hole at the front of the reducer relative to the axis of the motor stator mounting hole ranges from 0.003 mm to 0.005 mm.

[0071] The composite geared motor housing produced by the above processing method has a complete three-dimensional cooling channel 3 with a smooth inner wall, a strong bimetallic interface, and key dimensional and positional tolerances that meet the assembly requirements of precision reducers.

[0072] Comparative Example 1 This comparative example provides a conventional integrated all-cast iron geared motor housing. The housing is entirely made of QT500-7 ductile iron, with conventional heat dissipation fins on the outer surface, but no three-dimensional cooling channels inside, and no outer aluminum-based alloy structure.

[0073] After two hours of continuous full-load operation under conditions of constant stator heating power of 800 watts, ambient temperature of 25 degrees Celsius, and natural air cooling, infrared thermal imaging showed that the highest temperature of the housing wall near the reducer's lubricating oil cavity reached 85.4 degrees Celsius, which is close to the upper limit of the allowable operating temperature of commonly used special lubricating greases. When the outer volume of the all-cast iron housing is the same as in Example 1 (outer diameter 130 mm, length 180 mm), the blank weighs 8.65 kg. This comparative example shows that although a single iron-based alloy housing has good rigidity and shock resistance, its heat dissipation capacity is insufficient, resulting in excessively high temperatures on the wall surface near the reducer's oil cavity.

[0074] Comparative Example 2 This comparative example provides an integrated all-aluminum geared motor housing. The housing is entirely cast from ZL101A cast aluminum alloy, with internally machined spiral cooling channels. The all-aluminum housing is lightweight and has good heat dissipation; however, due to the low elastic modulus of aluminum-based alloys, under a radial concentrated force of 15000 N simulating 300% of the rated peak torque, nonlinear static simulation using Abaqus software shows that the radial deformation at the root circle of the internal gear ring base is significantly greater than in Example 1, exceeding the lower limit of the allowable runout tolerance for the cycloidal pinwheel meshing backlash, resulting in decreased transmission accuracy. This comparative example demonstrates that while a single aluminum-based alloy housing offers good heat dissipation and lightweighting, its insufficient rigidity makes it difficult to withstand the strong alternating impact loads at the reducer end.

[0075] Comparative Example 3 This comparative example provides a bimetallic composite shell, which differs from the first embodiment in that it does not have a porous microcrystalline ceramic layer 41 and laser-textured micro-pits 11. The outer aluminum-based alloy is directly cast onto the surface of the inner cast iron skeleton, which has been roughened by sandblasting, and does not form a gradient transition structure of thermal expansion coefficient and a cross-scale mechanical interlocking network.

[0076] In temperature cycling tests, the composite shell was repeatedly heated to 120 degrees Celsius and cooled to room temperature. After several cycles, interface sounds and local gaps appeared between the outer aluminum-based alloy and the inner cast iron skeleton. Upon sectioning, interface delamination was observed. This comparative example demonstrates that relying solely on the direct bonding of the iron-based alloy and aluminum-based alloy without a gradient transition structure for thermal expansion coefficients and a cross-scale mechanical interlocking network, the bimetallic interface is unable to withstand the shear stress generated by temperature cycling and is prone to delamination.

[0077] Comparative Example 4 This comparative example uses a straight-tube spiral flow channel with a constant cross-section, meaning the cross-section of the three-dimensional cooling channel 3 does not gradually change along the spiral direction, and the cross-sectional shrinkage ratio is 1.00. The remaining structure is the same as in Example 1. Under the same simulation boundary conditions as in Example 1, the convective heat transfer coefficient of the straight-tube flow channel with a constant cross-section is approximately 3150 W / m² Kelvin, and the channel pressure drop is approximately 14.5 kPa. In contrast, when the cross-sectional shrinkage ratio in Example 1 is 1.65, the convective heat transfer coefficient is approximately 6950 W / m² Kelvin, and the channel pressure drop is approximately 34.5 kPa. Although the straight-tube flow channel with a constant cross-section has lower flow resistance, its convective heat transfer coefficient is insufficient, and the temperature drop near the oil chamber of the reducer is less than that in Example 1.

[0078] Reference Figure 4 As shown in Table 1, multiple simulations were performed with varying cross-sectional area reduction ratios. When the cross-sectional area reduction ratio increased from 1.00 to 1.65, the convective heat transfer coefficient increased from 3150 W / m² Kelvin to 6950 W / m² Kelvin, an increase of approximately 1.2 times, while the flow channel pressure drop only increased from 14.5 kPa to 34.5 kPa, remaining within the head range of commonly used micro pumps. When the cross-sectional area reduction ratio exceeded 2.00, the growth of the convective heat transfer coefficient plateaued. When the cross-sectional area reduction ratio increased from 2.00 to 2.15, the convective heat transfer coefficient only increased from 7580 W / m² Kelvin to 7810 W / m² Kelvin, while the flow channel pressure drop increased sharply from 68.3 kPa to 105.4 kPa. When the cross-sectional area reduction ratio reached 2.40, the flow channel pressure drop reached 168.0 kPa, and localized cavitation occurred. The above results indicate that a cross-sectional area reduction ratio of 1.35 to 2.15 is a reasonable range that balances heat transfer enhancement and flow resistance control, 1.50 to 1.80 is the optimal range for overall energy efficiency ratio, and around 1.65 is the peak point for energy efficiency.

[0079] Table 1. Effect of Section Reduction Ratio on Heat Dissipation Performance

[0080] Performance testing The composite geared motor housing prepared in Example 1 was compared with the all-cast iron housing in Comparative Example 1.

[0081] Regarding the lightweighting indicators, the outer envelope volume of the shell was kept consistent (outer diameter 130 mm, length 180 mm). The mass attributes were extracted using three-dimensional software and weighed using a high-precision electronic platform scale. The weight of the all-cast iron shell in Comparative Example 1 was 8.65 kg, and the weight of the composite shell in Example 1 was 5.62 kg, resulting in a weight reduction of approximately 35%.

[0082] Regarding thermal performance, a thermal-fluid coupling model was established based on Ansys Fluent software. The ambient temperature was 25 degrees Celsius, and the simulated constant heating power of the motor stator was 800 watts. In Example 1, a 50% ethylene glycol aqueous solution at 25 degrees Celsius and a flow rate of 1.5 liters per minute was introduced, and the physical prototype underwent a steady-state test with continuous full-load operation for 2 hours using an infrared thermal imager. In Comparative Example 1, the highest wall temperature near the reducer lubrication oil chamber was 85.4 degrees Celsius under natural air cooling conditions. In Example 1, the highest wall temperature at the same location stabilized at 69.8 degrees Celsius, a decrease of approximately 15.6 degrees Celsius. It should be noted that the temperature rise data includes predictions based on computational fluid dynamics and thermal-fluid coupling simulations, which were verified by infrared thermal imaging testing of the physical prototype.

[0083] In terms of machining accuracy, a Hexagon coordinate measuring machine was used with the center axis of the motor stator mounting hole as reference A to measure the coaxiality of the high-precision bearing mounting hole at the front end of the reducer. Ten finished products from Example 1 were randomly sampled and inspected. The coaxiality error was distributed between 0.003 mm and 0.005 mm, which met the assembly requirements of precision RV reducers and harmonic reducers.

[0084] Regarding stiffness, using Abaqus nonlinear statics simulation software, an ultimate impact load equivalent to 300% of the rated peak torque (radial concentrated force 15000 N) was applied to the inner gear ring base of the housing in Example 1. The simulation contour plot shows that the maximum microscopic radial deformation of the inner load-bearing skeleton 1 at the tooth root circle is approximately 0.0076 mm, which is lower than the lower limit of the allowable runout tolerance for the cycloidal pinwheel meshing backlash. This deformation data is a simulation result and can be further verified through strain testing of a physical prototype.

[0085] The test results above show that the composite geared motor housing of Example 1 achieves good comprehensive performance in four dimensions: lightweight, heat dissipation, precision and rigidity.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A composite reduction motor housing characterized by, It includes an inner load-bearing frame and an outer heat-conducting shell covering the outer surface of the inner load-bearing frame; The inner load-bearing frame is made of iron-based alloy, and the outer heat-conducting shell is made of aluminum-based alloy. The thermal conductivity of the inner load-bearing frame is lower than that of the outer heat-conducting shell, so as to form a low thermal conductivity barrier between the motor stator mounting position and the reducer oil cavity. A three-dimensional cooling channel is provided between the outer heat-conducting shell and the inner support frame, spirally extending around the motor stator mounting position. When the heat generated by the motor stator is conducted along the inner support frame towards the reducer oil cavity, it is laterally intercepted by the three-dimensional cooling channel at the interface between the inner support frame and the outer heat-conducting shell. The cross-section of the three-dimensional cooling channel changes periodically along the spiral extension direction, and alternately forms a fluid acceleration section with a shrinking cross-sectional area and a diffusion section with a gradually expanding cross-sectional area along the spiral direction. The fluid acceleration section constitutes a Venturi throttling structure. When the coolant flows through the fluid acceleration section, it is accelerated and washes away and thins the thermal boundary layer of the inner wall of the three-dimensional cooling channel. When it flows through the diffusion section, it decelerates and restores pressure. At the interface between the outer heat-conducting shell and the inner support frame, a transition structure is provided in which the coefficient of thermal expansion increases in a gradient from the inner support frame to the outer heat-conducting shell. The transition structure includes a porous microcrystalline ceramic layer grown in situ on the outer surface of the inner support frame, and a diffusion bonding region formed by the aluminum-based alloy of the outer heat-conducting shell penetrating into the pores of the porous microcrystalline ceramic layer and metallurgically diffusion bonding with the porous microcrystalline ceramic layer. The heat intercepted by the three-dimensional cooling channel is transferred to the outer heat-conducting shell after enhanced convective heat transfer in the fluid acceleration section, and then diffused at a uniform temperature by the outer heat-conducting shell.

2. The composite geared motor housing according to claim 1, characterized in that, The flow passage section of the three-dimensional cooling flow passage is elliptical, and the ratio of the maximum cross-sectional area of the three-dimensional cooling flow passage to the minimum cross-sectional area of the fluid accelerating section is .

3. The composite geared motor housing according to claim 2, characterized in that, The ratio of the maximum cross-sectional area to the minimum cross-sectional area is: Within this ratio range, the Venturi effect of the fluid acceleration section increases the convective heat transfer coefficient by more than two times relative to a straight pipe with a constant cross-section, while the flow resistance pressure drop remains within the head range of the coolant supply device.

4. The composite geared motor housing according to claim 1, characterized in that, The fluid acceleration section and the diffusion section are alternately distributed along the spiral direction with a period of one pitch, causing the coolant to undergo one acceleration-diffusivity cycle and periodically disturb the thermal boundary layer within each pitch cycle; the pitch of the three-dimensional cooling channel is... The equivalent diameter of the three-dimensional cooling channel is .

5. The composite geared motor housing according to claim 1, characterized in that, The outer surface of the inner support skeleton is formed with an array of laser texturing micro-pits recessed into the inner support skeleton matrix. The porous microcrystalline ceramic layer covers the outer surface of the inner support skeleton and the inner wall of the laser texturing micro-pits. The aluminum-based alloy of the outer heat-conducting shell fills the laser texturing micro-pits and is continuously integrated with the aluminum-based alloy that penetrates into the pores of the porous microcrystalline ceramic layer, forming a mechanical interlocking network spanning the micrometer to hundred-micrometer scale. The aperture of the laser-etched micro-pit is The center-to-center distance between adjacent laser-textured micropits is The depth of the laser-textured micro-pits is ; The thickness of the porous microcrystalline ceramic layer is The porosity of the porous microcrystalline ceramic layer is The average pore size of the porous microcrystalline ceramic layer is .

6. The composite geared motor housing according to claim 1, characterized in that, The inner load-bearing frame is made of QT500-7 ductile iron or 42CrMo alloy steel, and the outer heat-conducting shell is made of ZL101A cast aluminum alloy.

7. A method for processing the composite geared motor housing as described in claim 1, characterized in that, Includes the following steps: S1. Based on the preset three-dimensional cooling channel shape, a spiral sand core is integrally formed using additive manufacturing process; the sand core has the tensile strength required to support the spiral cantilever structure at room temperature, and the sand core has a residual strength that can be removed by the fluid after solidification upon contact with molten aluminum alloy. S2. Position the sand core nested on the outer surface of the iron-based alloy inner layer bearing skeleton, and place the nested inner layer bearing skeleton in the casting cavity; S3. Perform interface composite modification treatment on the outer surface of the inner layer support skeleton: First, use laser to process the outer surface of the inner layer support skeleton to form a laser texturing micro-pit array, and then perform micro-arc oxidation treatment on the surface of the inner layer support skeleton with the laser texturing micro-pits to grow a porous microcrystalline ceramic layer in situ on the outer surface of the inner layer support skeleton and the inner wall of the laser texturing micro-pits. S4. After evacuating the casting cavity, molten aluminum-based alloy liquid is injected into the casting cavity under low pressure, so that the aluminum-based alloy liquid simultaneously penetrates into the micropores of the porous microcrystalline ceramic layer and the laser texturing micro-pits under low pressure. After pressure holding and solidification, an outer heat-conducting shell is formed that is metallurgically and mechanically combined with the inner layer load-bearing skeleton. S5. After demolding, remove the collapsed sand core to obtain a composite shell blank with the three-dimensional cooling channels inside. S6. Using the axis of the motor stator mounting hole as a reference, perform five-axis linkage adaptive precision machining on the composite housing blank.

8. The processing method for the composite geared motor housing according to claim 7, characterized in that, In step S1, the raw materials for forming the sand core include Head The target pearl sand, accounting for a certain percentage of the mass of the pearl sand. The modified furan resin binder and a sulfonic acid microcapsule curing agent comprising 15% to 25% of the mass of the modified furan resin binder; the tensile strength of the molded sand core at room temperature is... After the aluminum-based alloy liquid is cast and solidified, the residual strength of the sand core decreases to the following.

9. The processing method for the composite geared motor housing according to claim 7, characterized in that, In step S3, the micro-arc oxidation treatment is performed using a silicate-aluminate composite electrolyte, with a pulse voltage of [voltage value missing]. The current density is Processing time is The aperture of the laser-textured micro-pit is... The center-to-center distance of the laser-textured micropits is The depth of the laser-textured micro-pits is .

10. The processing method for the composite geared motor housing according to claim 7, characterized in that, In step S4, the inner supporting skeleton is preheated to [temperature value missing] before being placed in the casting cavity. The pouring temperature of the aluminum-based alloy liquid is The vacuum degree of the casting cavity is The low-pressure injection pressure is And the boost rate is The pressure holding time is The solidification temperature gradient is ; In step S5, an N-methylpyrrolidone organic solvent is used and supplemented with The sand core is removed by ultrasonic vibration, and the temperature of the organic solvent is [temperature missing]. The clearing time is .

Citation Information

Patent Citations

  • Water-cooled motor case

    CN201887590U

  • Rotating electrical machine and method for manufacturing rotating electrical machine

    US20220263378A1